LEPTIN : FIGHTS AGAINST OBESITY - Aslam, Muhammad (Pakistan Journal of Physiology, 2006)
Leptin (from the Greek leptos, meaning thin), It was originally identified as the gene defect responsible for the obesity syndrome in mice discovered in 1994.1 It is a 167-amino acid protein hormone with important effects in regulating body weight, metabolism and reproductive function. Leptin, The genetic defect of ob/ob mice was first described in the 1950s as the spontaneous mutation that causes a severe obese phenotype due to both overeating and decreased energy expenditure. The gene was named ob and the obese mice carrying the mutation were called ob/ob mice. Because a defect in leptin led to overeating and obesity, leptin was proposed to be a satiety factor. Circulating leptin levels are directly related to adipose tissue mass. High leptin levels signal the presence of sufficient energy stores to sites in the central nervous system, which respond by reducing appetite and increasing energy expenditure, preventing severe obesity. Therefore, leptin signals the nutritional status from the periphery to the area of the brain involved in the homeostasis of energy balance. However, the primary function of leptin may not be as a satiety factor. Leptin treatment at physiological levels reduces eating (and increases energy expenditure) by ob/ob mice to the levels of normal mice, but it does not cause satiety (end of eating). Higher doses of leptin are required to decrease food intake in normal animals. The samerelationships are true in humans with the ob gene defect and normal humans. Leptin levels are also modulated acutely. For example, leptin levels change rapidly with feeding or fasting disproportionately to the changes in fat depot. Therefore, leptin is not just a readout of the fat stores. Leptin is expressed predominantly by adipocytes, which fits with the idea that body weight is sensed as the total mass of fat in the body, it is a key mediator in the regulation of food intake and energy expenditure. Smaller amounts of leptin are also secreted by cells in the epithelium of the stomach and in the placenta. Leptin receptors, which have sequence homology to members of the gp130 cytokine receptor super family, are widely distributed throughout the body, and its mRNA is known to be expressed in hematopoietic cells and lymphocytes. Leptin receptors are highly expressed in areas of the hypothalamus known to be important in regulating body weight, as well as in Tlymphocytes and vascular endothelial cells. Its level is directly related to the amount of adipose tissue. Leptin inhibits food intake by central action on the hypothalamus Leptin’s functions are quite pleiotropic, and it is implicated in a variety of cellular processes, including the modulation of immune cell function. Leptin is structurally related to the longchain helical cytokine family, which includes IL-2, IL-12, and growth hormone. Serum leptin levels decrease during starvation, and leptin has been proposed to be a major regulator of the central nervous system-mediated adaptation to starvation. Absence of leptin is responsible for the obese phenotype of ob/ob mice, and administration of this hormone to these animals reverses many of the endocrine defects. Short-term fasting results in a rapid and marked decline in leptin levels out of proportion to the loss of fat mass, and it has been proposed that this most like ly serves as an adaptive mechanism to promote survival and limit procreation during starvation. Body adiposity has been shown to be a major determinant of circulating leptin, an adipocyte-derived hormone involved in body weight regulation. Whereas women have higher leptin concentrations, even after correction for body fat mass, in both genders the Subcutaneous Fat depot seems to be a stronger predictor of leptin levels than Intra-Abdominal Fat. Furthermore, studies in rodents support a possible role of leptin in regulating adiponectin, showing that fasting, a state that acutely decreases leptin expression and its serum concentration, also decreases adiponectin gene expression in adipose tissue, whereas refeeding normalizes the expression of both hormones.